Perovskite With Tunable Active-Sites Oxidation State by High-Valence W for Enhanced Oxygen Evolution Reaction - Yan, Jiabiao; Xia, Mingkun; Zhu, Chenguang; Chen, Dawei; Du, Fanglin (Frontiers in Chemistry, 2022)
Perovskite oxides have been established as a promising kind of catalyst for alkaline oxygen evolution reactions (OER), because of their regulated non-precious metal components. However, the surface lattice is amorphous during the reaction, which gradually decreases the intrinsic activity and stability of catalysts. Herein, the precisely control tungsten atoms substituted perovskite oxides (Pr0.5Ba0.5Co1-xWxO3-δ) nanowires were developed by electrostatic spinning. The activity and Tafel slope were both dependent on the W content in a volcano-like fashion, and the optimized Pr0.5Ba0.5Co0.8W0.2O3-δ exhibits both excellent activity and superior stability compared with other reported perovskite oxides. Due to the outermost vacant orbitals of W6+, the electronic structure of cobalt sites could be efficiently optimized. Meanwhile, the stronger W-O bond could also significantly improve the stability of latticed oxide atoms to impede the generation of surface amorphous layers, which shows good application value in alkaline water splitting.